NEXUS BETWEEN PERFORMANCE MEASUREMENT SYSTEMS AND PSYCHOLOGICAL EMPOWERMENT IN THE PHARMACEUTICAL INDUSTRY - Ishfaq, Umer; Batool, Saima; Salahuddin, Sultan; Alam, Muhammad Mehboob; Abid, Seemab (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: The purpose of this study is to examine the impact of interactive performance measurement systems on the employees’ psychological empowerment in the pharmaceutical industry in Pakistan. Methodology: This research used a survey and the respondents were medical representative/detailer employees in the pharmaceutical firms in Pakistan. Data was collected from 390 responding out of 650 distributed questionnaires and analyzed by using Smart PLS. Main Findings: The outcomes of this study showed that the interactive performance measurement system has a positive and significant impact on the employees’ psychology in the pharmaceutical industry in Pakistan. Applications of the study: This research showed that the interactive performance measurement system is a tool that can open the communication network between the managers and the employees which must be supported by maximum employees’ psychological empowerment so that can reach the company’s vision and mission, especially for the medical representative/detailer in the pharmaceutical company in Pakistan. Novelty/Originality of the study: This research showed how important psychological empowerment is for lower-middle level employees especially for the medical representative/detailer in order to improve the company’s performance by using the interactive performance measurement system in a pharmaceutical company in Pakistan.